2021
DOI: 10.3390/plants10020234
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Photosynthetic Iron-Use Efficiency Is an Important Trait of Hordeum vulgare for Adaptation of Photosystems to Iron Deficiency

Abstract: Leaf iron (Fe) contents in Fe-deficiency-tolerant plants are not necessarily higher than that in Fe-deficiency-susceptible ones, suggesting an unknown mechanism involved in saving and allowing the efficient use of minimal Fe. To quantitatively evaluate the difference in Fe economy for photosynthesis, we compared the ratio of CO2 assimilation rate to Fe content in newly developed leaves as a novel index of photosynthetic iron-use efficiency (PIUE) among 23 different barley (Hordeum vulgare L.) varieties. Notabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In accordance with these results that confirm the importance of Fe use efficiency in shoots, Zhao et al ( 2020 ) suggested that the iron efficiency is attributed to an iron activation mechanism in leaves. Saito et al ( 2021 ) demonstrated that varieties of barley originating from alkaline soils increased their photosynthetic iron use efficiency in response to Fe‐deficiency. They suggest that the ability of Fe‐deficiency tolerant varieties of barley to increase their iron use efficiency is related to optimizing the electron flow downstream of PSII, including cytochrome b6f and photosystem I. Hantzis et al ( 2018 ) and Kroh and Pilon ( 2020 ) suggested that cyt b6f and PSI are the most Fe‐requiring photosynthetic apparatus and the primary sufferer of Fe‐deficiency in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with these results that confirm the importance of Fe use efficiency in shoots, Zhao et al ( 2020 ) suggested that the iron efficiency is attributed to an iron activation mechanism in leaves. Saito et al ( 2021 ) demonstrated that varieties of barley originating from alkaline soils increased their photosynthetic iron use efficiency in response to Fe‐deficiency. They suggest that the ability of Fe‐deficiency tolerant varieties of barley to increase their iron use efficiency is related to optimizing the electron flow downstream of PSII, including cytochrome b6f and photosystem I. Hantzis et al ( 2018 ) and Kroh and Pilon ( 2020 ) suggested that cyt b6f and PSI are the most Fe‐requiring photosynthetic apparatus and the primary sufferer of Fe‐deficiency in plants.…”
Section: Discussionmentioning
confidence: 99%
“…They suggest that the ability of Fe‐deficiency tolerant varieties of barley to increase their iron use efficiency is related to optimizing the electron flow downstream of PSII, including cytochrome b6f and photosystem I. Hantzis et al ( 2018 ) and Kroh and Pilon ( 2020 ) suggested that cyt b6f and PSI are the most Fe‐requiring photosynthetic apparatus and the primary sufferer of Fe‐deficiency in plants. Saito et al ( 2021 ) postulate that the key mechanism for increased photosynthesis iron use efficiency under Fe‐deficiency to exist downstream of PSII seems reasonable. Nevertheless, Durum wheat is known by its capacity of roots release exudates into the rhizosphere (strategy II plant releasing PS).…”
Section: Discussionmentioning
confidence: 99%
“…However, the actual Fe uptake rate has not been broadly surveyed in many species or genotypes using the same experimental system. We recently reported that the amount of acquired Fe may not always be the sole determinant of tolerance to Fe deficiency, and that acclimation of chloroplasts to low-Fe conditions also contributes to tolerance among barley cultivars [ 11 ]. Some Fe-deficiency-tolerant cultivars may exert tolerance depending on the effective Fe uptake, whereas others depend on Fe sparing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fluorescent material was replaced to obtain better luminescence because the uptake of trace elements, such as Fe, was low. The three barley cultivars used in this work were “Sarab 1 (SRB)” with very strong Fe-deficiency tolerance, “Ehimehadaka 1 (EHM)” with strong tolerance, and “Ethiopia 2 (ETH)” with weak tolerance [ 11 ]. SPAD values of EHM and ETH significantly decreased when cultivated with 3 μM Fe nutrient solution and ETH exhibited very severe chlorosis with 1 μM Fe, whereas SRB showed no obvious chlorosis even under the 1 μM Fe condition ( Figure 1 in [ 11 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation